The Evaluative - Formalism of the New Code of Civil Procedure - Dias, Luciano Souto (2016)
This research aims to discuss the evaluative-formalism and its incidence in the text of the new Brazilian Civil Procedure Code, sanctioned by the president and that, from March 2016 on,  will  replace  the  current  regulation.  CPC/15  presents  significant  procedural  and proceeding innovations, leading to new paradigms, making the adoption of practices that points the effective consideration of formalism technique observed in the process visible. The evaluative-formalism contributes to the optimization of the procedure, in order to safeguard the effectiveness of judicial protection, with dialectical and historical-comparative, through theoretical argument and literature review of national and foreign works, the text highlights the evolution of legal thought as the matter under discussion and, objectively, discusses the innovations resulting from the new procedural regulation which highlights the evaluative- formalism as this methodology in text and context in the New Code of Civil Procedure.